G156(P) Towards the barnahus (child house) multi-agency model of care for child sexual abuse: the value of a family therapist and a young person advocate. (12th March 2018) - Rodrigues, S; Wong, M; Weedon, A; Qasir, S; Benson, A; Hodes, D
Abstract : Background: Lack of appropriate support following sexual abuse can lead to long-term emotional, physical and social problems. The Child House will be launched in 2018. As a first step, a Child/Young Person Advocate (CA) and a Family Therapist (FT) joined the Paediatrician in an established clinic for the assessment of historic child sexual abuse. Objectives: To determine the value of integrated psychosocial and advocacy services in the clinic. Method: A retrospective review of notes for 20 patients before integration (BI), compared with 22 patients after integration (AI) was carried out. Outcome measures included emotional and behavioural needs and referrals. Results: In the BI versus A1 cohort, 8 (40%) had emotional problems and 3 (15%) were in police proceedings versus 12 (55%) and 3 (13%) respectively. Only two patients were referred to their local Mental Health Service before integration. In the AI cohort, 10 patients had the FT in the paediatric consultation and one had a further appointment in a week, five in two or more weeks and four were referred to another FT for psychological support. Two made a new disclosure in the clinic and were referred to social care. Six patients had the CA present at the paediatric consultation for support with the court process and one had an appointment later. One parent was referred for domestic violence support. Conclusions: This study showed having the FT and CA join the consultation provided 17 of 22 (78%) patients, immediate or early management for mental health needs and police proceedings. A multidisciplinary team supports the varied needs of our patients and is at the centre of the Barnahus model. Future research will review the child and parent opinion about this model and also the outcomes for the child.